China carbon emission accounts 2020-2021 - Xu, Jinghang; Guan, Yuru; Oldfield, Jonathan; Guan, Dabo; Shan, Yuli (Applied energy, 2024)
In the past a few years, the outbreak of the COVID-19 epidemic has significantly changed global emission patterns and increased the challenges in emission reduction. However, a comprehensive analysis of the most recent trends of China's carbon emissions has not been conducted due to a lack of up-to-date emission accounts by regions and sectors. This study compiles the latest CO2 emission inventories for China and its 30 provinces during the epidemic (2020−2021), following the administrative-territorial approach from the International Panel on Climate Change (IPCC). Our inventories cover energy-related emissions from 17 types of fossil fuel combustion and cement production across 47 economic sectors. To provide a holistic view of emission patterns, we esitamted consumption-based emissions in China. We find that the COVID-19 epidemic led to a 50% reduction in the growth rate of territorial emissions in 2020 compared to 2019. This trend then reversed in 2021 as lockdown measures gradually relaxed. Our study reveals the impact of the rapid expansion of exports, driven by epidemic prevention materials and “stay-at-home economy” products on widening the differences between territorial- and consumption-based emissions. Our study offers a timely blueprint for designing strategies towards carbon peak and neutrality, especially in the context of sustainable recoveries and carbon mitigation post-pandemic. •Accounting of IPCC administrative territorial emissions from fossil fuels and cement production for China and its provinces in 2020–2021•Accounting of consumption-based emissions for China from 2002 to 2020•Revealing the dynamic impact of COVID-19 on China's carbon emissions